Differential effectiveness of two creativity techniques in enhancing creativity motivation of some Nigerian adolescent prisoners (2002)
This study investigated the differential effectiveness' of Six Thinking Hats and Akinboye's Prqctical Creativity At Work (APCAW) techniques in enhancing the creativity of some Nigerian adolescent prisoners. The study sample was 135 convicted adolescent prisoners whose ages ranged from 18-21 with a mean of 19.5 randomly selected from Agodi Prison, Ibadan, Oyo State and Ilesa Prison, Osun State. The subjects were randomly assigned to the two intervention conditions and control group. The treatment lasted for six weeks of twelve sessions. A 3 x 3 experimental design was adopted. The validated instruments namely: the Creativity Motivation Scale in lbadan Creativity Assessment Scale (ICAS) and Self Concept Scale in the Adolescent Personal Data Inventory (APDI) were used. The results indicated that subjects exposed to treatments performed significantly better than the control group on measure of creativity motivation of the subjects. On differential effectiveness basis, however, APCAW technique took the lead. On the basis of the finding, it was suggested that Nigerian Prisoners should undergo training in creativity so as to be adequately equipped to cope with life after incarceration